DEVELOPING READING SKILL THROUGH CONTEXTUAL TEACHING AND LEARNING - Marzuki, Abdul Gafur (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2016)
This research aims at finding the influence of Contextual Teaching and Learning toward the students’ learning achievement. The subject of the study was 25 eighth grade students at SMP Negeri 9 Palu. The research was conducted in two cycles through the steps of planning, acting, observing, and reflecting. The researcher collected the data by using observation sheets, field notes, questionnaire, portfolio, and test. The data were analyzed quantitative and qualitatively. The result of achievement test showed that in cycle 1 there were only 17 students (68%) who got score greater than 65, whereas in cycle 2 there were 21 students (84%) who got score greater than 65. The action was stopped after the third meeting in cycle 2, because the result of students’ learning achievement had met the criteria of success. Based on the result of data analysis, the application of Contextual Teaching and Learning was effective to develop the reading skill.